Faktor-Faktor yang Mempengaruhi Produksi Padi Sawah (Oriza sativa L) di Kelurahan Unaasi Kecamatan Anggaberi Kabupaten Konawe - Muliyanti, Sri; Rianse, Usman; Abdullah, Weka Gusmiarty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the effect of production factors on the production of paddy rice in the Unaasi Sub-District of Anggaberi Sub-District, Konawe Regency. The population in this study were 220 lowland rice farmers. The sample in this study amounted to 69 respondents who were determined by the simple random sampling method. The analytical method used is regression analysis with the Cobb-Douglass production function equation. The results of this study indicate that the average yield of wetland rice from 69 respondents in the Unaasi Village of Anggaberi Subdistrict, Konawe Regency was 301 kg/ha with the highest yield of 500 kg/ha and the lowest yield of 100 kg/ha. The factors of production (land area, seeds, and fertilizer score) affect the production of wetland rice in the Unaasi Subdistrict, Anggaberi District, Konawe Regency. While the production factors (spontaneous pesticides, labor, and mutual cooperation) did not affect the production of paddy rice farming in the Unaasi Sub-District of Anggaberi District, Konawe Regency. This indicates that there are still opportunities for lowland rice farmers to increase their production output by optimizing the factors of production they have.